1993
DOI: 10.1093/infdis/167.4.857
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin, Iron, and Serum Lipids Enhance or Inhibit Mycobacterium avium Replication in Human Macrophages

Abstract: Mycobacterium avium grows exponentially over 7 days in human macrophages when they are cultured in serumless medium. Normal serum inhibits this replication. When serum lipids were extracted using chloroform, the inhibitor was present in the lipid-free component. The lipid extract significantly enhanced M. avium replication. Iron (Fe2+) added at 8-80 micrograms/mL to infected macrophage cultures in serum resulted in enhanced mycobacterial replication. Serum-induced inhibition of bacterial growth in serumless me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Since BfrA and BfrB are the only two iron storage proteins in M. tuberculosis, their absence perhaps results in the insufficient supply of iron to the cell, leading to the concomitant attenuation of growth. The attenuation of M. tuberculosis growth in macrophages in response to the deficiency of iron in host macrophages has been reported earlier in several studies (9,11).…”
Section: Discussionsupporting
confidence: 74%
“…Since BfrA and BfrB are the only two iron storage proteins in M. tuberculosis, their absence perhaps results in the insufficient supply of iron to the cell, leading to the concomitant attenuation of growth. The attenuation of M. tuberculosis growth in macrophages in response to the deficiency of iron in host macrophages has been reported earlier in several studies (9,11).…”
Section: Discussionsupporting
confidence: 74%
“…L. pneumophila and E. chaffeensis are sensitive to intracellular iron deprivation, and as a consequence, alterations in human monocyte iron metabolism induced by IFN␥ will influence their growth (1,2,7). In a fashion similar to L. pneumophila, intracellular iron dependence in mononuclear phagocytes has been demonstrated for Francisella tularensis (3,8), and iron has been found to have a permissive effect on the intracellular growth of Mycobacterium avium intracellulare (5). In contrast, iron has been found to have both positive and negative effects on intracellular growth of Listeria monocytogenes depending on intracellular iron concentrations, and a negative effect on intracellular growth of Brucella abortus.…”
Section: Discussionmentioning
confidence: 91%
“…Iron has been shown to enhance, and in some cases suppress, the growth of various intracellular bacterial pathogens (1)(2)(3)(4)(5)(6)(7)(8). The availability of intracellular iron to these pathogens can be influenced by cytokines (1,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study demonstrates that the recombinant BCG(mbtB)30 strain which is unable to synthesize both mycobactin and carboxymycobactin retains the ability to multiply and survive within macrophages over the initial days of infection 14 . The importance of transferrin in mycobacterial iron acquisition is also evident from studies demonstrating that intraphagosomal M.tb siderophore knockout strains retained the ability to recruit and acquire iron by utilizing transferrin 5,14,15 . Other studies have demonstrated that ironsaturated transferrin promotes the replication of M. avium within the phagosome 15 .…”
mentioning
confidence: 96%
“…The importance of transferrin in mycobacterial iron acquisition is also evident from studies demonstrating that intraphagosomal M.tb siderophore knockout strains retained the ability to recruit and acquire iron by utilizing transferrin 5,14,15 . Other studies have demonstrated that ironsaturated transferrin promotes the replication of M. avium within the phagosome 15 . Elevated serum iron and high levels of ironsaturated transferrin are known to have a strong correlation with the exacerbation of tuberculosis in both mouse models and patient studies 3,[16][17][18][19][20] .…”
mentioning
confidence: 96%